Removable Partial Denture with dual path of insertion: clinical case report - Uemura, Eduardo Shigueyuki; Silva, João Mauricio Ferraz da; Kojima, Alberto Noriyuki; Torres, Carlos Rocha Gomes; Vieira, Cleiton Santos (Brazilian Dental Science, 2017)
Removable Partial Dentures (RPD) with dual path of insertion are designed to overcome conventional RPD esthetic limitations, through the use of proximal undercuts for rigid direct retainers. Therefore, dual path RPD is considered a variation of conventional RPD. This paper reports a clinical case where proper function as well as excellent esthetics were obtained with this type of RPD.